PREDICTING THE DEVELOPMENT OF COGNITIVE IMPAIRMENT IN PATIENTS AFTER COVID-19 INFECTION - Filiuk, I.O.; Kalbus, O.I.; Shastun, N.P.; Hudarian, Y.I.; Makarov, S.O. (World of Medicine and Biology, 2025)
The study focused on predicting the development of cognitive impairment in patients following COVID-19. The study involved 100 patients, 69 in the main group and 31 in the control group. In terms of gender composition, men predominated – 60 people. According to the results of a comprehensive clinical and neurological examination, as well as neuropsychological examination, which considers quality of life indicators and laboratory examination, specifically the level of phosphorylated neurofilament, this factor is identified as a predictor of the development of the neurodegenerative process. Patients in the main group (n=69) were divided into 2 subgroups based on the level of neurofilament: the NfL-N subgroup with a concentration not exceeding the norm and the NfL-P subgroup with a concentration above the norm. A predictive model for the development of cognitive impairment in patients with COVID-19 has been developed to improve early diagnosis of neurodegenerative diseases.